329 Hyperthermic intraperitoneal chemotherapy (HIPEC) in ovarian cancer. (18th September 2019) - Salvai, M; Riege, RM; Costa, J; Santillan, G; Rosso, M
Abstract : Objectives: To evaluate the disease-free survival rate in patients with ovarian cancer treated with hyperthermic intraperitoneal chemotherapy (HIPEC) and to analyze the complications related to the procedure. Methods: Retrospective, longitudinal observational study of patients diagnosed with ovarian cancer, who underwent cytoreduction surgery and intraoperative hyperthermic chemotherapy between January 1989 and January 2019, at the '''''Instituto de Ginecología''''' and '''''Grupo Gamma''''' of Rosario, Santa Fe, Argentina. Results: Of the total number of patients included (n: 43), 67.4% were alive without evidence of disease and 32.6% died because of their disease. The five-year disease-free survival was 68.5%. The prevalence of complications was 13.95% and they included grade 3–4 complications according to the toxicity scale. No deaths related to the technique were reported. Conclusions: Hyperthermic intraperitoneal chemotherapy is an efficient procedure. There was an apparent improvement in progression-free survival and overall survival with a low prevalence of complications.